A study on menstrual hygiene practices and knowledge among adolescent girls of Barpeta urban, Assam - Ashok Jyoti Deka; Mustaque Ahmed; Krishangee Bordoloi (Barpeta Obstetrics and Gynaecological Society, 2023)
Objective: The aim of the study was to assess the hygiene practices and knowledge regarding menstruation among adolescent girls and to determine the menstrual related health problems. Methodology: This was a cross-sectional study on 110 adolescent girls, who had attained menarche, selected from 10 schools in urban areas of Barpeta district. Data was collected by interview method with the help of pre-designed, pre-tested, structured schedule containing both open and closed questionnaire. Results: The study found that 89.1% girls knew menstruation was a normal physiological process whilst among them 89.8% did not know the cause and organ of menstrual bleeding. Absorbent material used by 87.3% was sanitary pad among which 51% disposed it in household burial pit. Both soap and water was used for cleaning genital areas in 87.3% of the girls. The most common complain during menstruation was pain abdomen (66.4%). School absenteeism for variable period was found in 35.4%. Conclusion: Menstrual hygiene practices in most of the adolescent girls were found to be nearly satisfactory however knowledge regarding menstruation was found to be inadequate. Various types of health problems were faced during menstruation. Therefore imparting education to the girls in schools and other health and wellness facilities regarding menstruation, menstrual hygiene practice and management of related health problems is highly recommended.